1981
DOI: 10.1071/bi9810347
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Scutellar Bristles of Drosophila Melanogaster ID. Long-Term Selection for High Bristle Number in Three further Lines Derived From the Oregon-RC Strain, Correlated Responses in Abdominal Bristles, lUld Changes in Regulation of the Scute Locu

Abstract: Results of selection over 135 generations for high scutellar bristle number in three further lines derived from Oregon-RC complement those on the four lines reported previously (Sheldon and Milton 1972). All lines differed widely in pattern of scutellar response, correlated response in abdominal and posterior central scutellar bristles, sex differences, and behaviour on relaxing selection, though the selection limits reached in the present three lines were lower than in the previous lines.The early scutellar r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…There are four scutellar bristles in most Drosophila species ( 49 ). In a previous study, skd 1 heterozygotes were found to have normal bristle numbers, whereas about a third of skd 1 heterozygotes in a dHcf HR1 background possessed extra scutellar bristles ( 43 ).…”
Section: Resultsmentioning
confidence: 99%
“…There are four scutellar bristles in most Drosophila species ( 49 ). In a previous study, skd 1 heterozygotes were found to have normal bristle numbers, whereas about a third of skd 1 heterozygotes in a dHcf HR1 background possessed extra scutellar bristles ( 43 ).…”
Section: Resultsmentioning
confidence: 99%
“…Selection on one trait may not necessarily yield the same pattern of correlated responses among a set of traits as selection on a different trait of the same set. Reasons for these nonreciprocal results include the existence ofgenetic asymmetries (Falconer, 1981 p. 192) at loci involved in the pleiotropic effects, nonadditive interactions among major and minor loci (Rendel, 1967;Sheldon and Milton, 1972), and differences in the precision with which a selection differential can be applied to each character (Falconer, 1981 p. 288). Furthermore, genetic correlations are particularly sensitive to changes in gene frequencies and, therefore, may change during the course of selection (Bohren et aI., 1966;Turelli, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…For example, M ACBEAN et al (1971) andM ILTON (1972) attribute to chromosome 3 the most importance in increasing the number of bristles in some lines ; so do R UBIO & A LBORNOZ (1982) for dorsocentral e.b. Others find chromosomes 1 and 2 more important (e.g.…”
Section: Discussionmentioning
confidence: 98%